1998
DOI: 10.3141/1632-07
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Major Freeway Reconstruction Projects: The Houston Experience

Abstract: Several steps in the planning, execution, and evaluation of the I-45 Pierce Elevated reconstruction in Houston provide a strong framework for preparing for projects that affect critical links in the nation’s transportation system. These elements include preconstruction traffic modeling, public information, and data collection before and during each phase of construction. Traffic modeling helped to prepare for construction by first developing delay numbers for the estimated user cost used in the A + B bidding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is affected by time of day, traffic volume, diverted traffic, number of travel lanes, number of closed lanes, and lane closure duration. Benz et al used computer models to simulate the travel delay during and after construction with delay difference converted into user cost (15). Therefore, it is suggested that the average system delay difference (ΔD s ) in hours per vehicle be estimated for a particular lane closure arrangement.…”
Section: Added User Cost Of Restoration Work Zonementioning
confidence: 99%
“…It is affected by time of day, traffic volume, diverted traffic, number of travel lanes, number of closed lanes, and lane closure duration. Benz et al used computer models to simulate the travel delay during and after construction with delay difference converted into user cost (15). Therefore, it is suggested that the average system delay difference (ΔD s ) in hours per vehicle be estimated for a particular lane closure arrangement.…”
Section: Added User Cost Of Restoration Work Zonementioning
confidence: 99%